The Distributional Impact of Taxes and Transfers : Evidence From Eight Developing Countries - Inchauste, Gabriela; Lustig, Nora (Washington, DC: World Bank, 2017)
The World Bank has partnered with the Commitment to Equity Institute at Tulane University to implement their diagnostic tool—the Commitment to Equity (CEQ) Assessment—designed to assess how taxation and public expenditures affect income inequality, poverty, and different economic groups. The approach relies on comprehensive fiscal incidence analysis, which measures the contribution of each individual intervention to poverty and inequality reduction as well as the combined impact of taxes and social spending.